Component and structure recombined natural bone repair material and preparation method thereof
By nano-native and combining natural cortical bone with PCL, bone repair materials are prepared using 3D printing technology, the problems of low utilization rate and insufficient biocompatibility of allogeneic cortical bones are solved, and good biocompatibility and repair are achieved Effect.
Patent Information
- Application Number
- CN202411607943.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
Existing bone repair materials have problems with low allocortical bone utilization, insufficient biocompatibility and poor repair results.
By crushing natural cortical bones to nanoscale, degreasing and decellularization treatments, combined with polyalpilot PCL, natural bone repair materials with recombinant components and structures were prepared using 3D printing technology.
It has achieved good biocompatibility of bone repair materials, easy tissue attachment and growth, and has significant repair effect, solving the limitations of traditional materials in large segments of bone repair.
Smart Images

Figure CN119455122A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of biomaterials, and in particular to a natural bone repair material with reorganized components and structure and a preparation method thereof. Background Art
[0002] Bone tissue is formed by osteoblasts secreting bone matrix and maturing into osteocytes wrapped in bone matrix. Among them, inorganic components (mainly hydroxyapatite, about 85%, calcium carbonate, about 10%, and 2-3% calcium fluoride) account for about 70% of the total weight, cells (osteoblasts, osteocytes and osteoclasts) account for about 2%, water accounts for about 10%, and organic components account for about 20-30%; the organic components are mainly collagen, 90% of the protein in the bone matrix is collagen, of which 97% is type I, and there are also II, V, XI and XIII collagen; other proteins in the bone matrix include glycoproteins such as alkaline phosphatase, bone sialoprotein, osteocalcin, osteopontin, fibronectin, etc.; proteoglycans also account for a small part of non-collagenous proteins and have compression resistance. Bone tissue is a lifelong dynamic self-renewal and reconstruction tissue. A certain range of bone damage (minor fractures, fractures without displacement) can be self-regenerated and repaired without human intervention. When it cannot be repaired by itself, surgical bone grafting is often required. However, current bone graft materials still have many limitations. Summary of the invention
[0003] The embodiments of the present application provide a natural bone repair material with reorganized components and structure and a preparation method thereof. The produced bone repair material has good biocompatibility, is easy for tissue attachment and growth, and has a good repair effect.
[0004] In a first aspect, the present invention provides a method for preparing a natural bone repair material having reorganized components and structures, the method comprising:
[0005] Step S111: crushing the natural cortical bone to produce cortical bone powder with a particle size of 300 to 500 microns; wherein the natural cortical bone is allogenic bone or xenogeneic bone;
[0006] Step S112: using a mixture of chloroform and methanol to defatted the cortical bone powder to obtain defatted bone powder;
[0007] Step S113: decellularizing the defatted bone powder using an elution solution to obtain decellularized bone powder;
[0008] Step S114: washing the decellularized bone powder until the pH value is 7.3-7.5, and producing freeze-dried bone powder by freeze-drying;
[0009] Step S115: grinding the freeze-dried bone powder again to produce nano bone powder with a particle size of less than or equal to 750 nanometers;
[0010] Step S2: mixing polycaprolactone PCL and the nano bone powder to form a bone powder solution; and performing 3D printing processing using the bone powder solution to produce a natural bone repair material with reorganized components and structure.
[0011] In some embodiments, step S2 specifically includes:
[0012] Step S211: heating and dissolving PCL at 140° C. to form a PCL solution, adding the nano bone powder to the PCL solution, and mixing to form the bone powder solution; wherein the weight ratio of PCL to the nano bone powder is 1:0.5-2.5;
[0013] Step S212: constructing a three-dimensional digital model of the bone defect scaffold;
[0014] Step S213: Fill the bone powder solution into the barrel of a 3D printer, and perform 3D single-line printing according to the three-dimensional digital model of the bone defect scaffold to produce the natural bone repair material with reorganized components and structure.
[0015] In some embodiments, for step S213, the parameters of the 3D single-line printing are: wire diameter 0.3-0.5 mm, barrel temperature 100-130°C, platform temperature 40°C, pneumatic pressure 0.5 MPa, filling spacing 0.8-1.5 mm, speed 3 mm / s, rotation angle 90, number of rotations 2 times, layer height 0.25-0.45 mm.
[0016] In some embodiments, the method further comprises:
[0017] Step S121: uniformly mixing the freeze-dried bone powder, hydrochloric acid solution and pepsin to produce a collagen solution;
[0018] Step S122: adding sodium chloride to the collagen solution, stirring until a white precipitate is precipitated, collecting the precipitate by centrifugation, and dissolving the precipitate in acetic acid to produce a solution to be treated;
[0019] Step S123: performing dialysis treatment on the solution to be treated to obtain collagen.
[0020] In some embodiments, step S2 specifically includes:
[0021] Step S221: using polycaprolactone PCL and the nano bone powder to form a bone powder solution, and using the bone powder solution as type A printing ink; wherein the weight ratio of the PCL to the nano bone powder is 1:0.5-2.5;
[0022] Step S222: dissolving the collagen in acetic acid to form a collagen gel, and adding recombinant human bone morphogenetic protein rh-BMP2 to the collagen gel to produce type B printing ink; wherein 50 mg of collagen is added to every 1 ml of the acetic acid, and 50 μg of rh-BMP2 is added to every 1 ml of the bone gel solution;
[0023] Step S223: constructing a three-dimensional digital model of the bone defect scaffold;
[0024] Step S224: Fill the type A printing ink into a high-temperature barrel and the type B printing ink into a low-temperature barrel, and perform 3D double-line printing according to the three-dimensional digital model of the bone defect scaffold to produce the natural bone repair material with reorganized composition and structure.
[0025] In some embodiments, in step S224, the printing setting parameters of type A printing ink are as follows: wire diameter 0.3-0.5mm, barrel temperature 100-130°C, platform temperature 40°C, pneumatic pressure 0.5Mpa, filling spacing 0.8-1.5mm, speed 3mm / s, rotation angle 90°, rotation number 2 times, layer height 0.25-0.45mm; the printing setting parameters of type B printing ink are as follows: wire diameter 0.21-0.26mm, barrel temperature 23°C, platform temperature 40°C, pneumatic pressure 0.1-0.5Mpa, filling spacing 0.8-1.5mm, speed 3-15mm / s, rotation angle 90°, rotation number 2 times, layer height 0.25-0.45mm, and X and Y axis translation 0.5mm.
[0026] In some embodiments, in step S121, the volume of hydrochloric acid solution used per gram of bone powder is 90-120 ml, the volume of pepsin used per gram of bone powder is 80-120 mg, the mixing time is 90-100 hours, and the concentration of the hydrochloric acid solution is 0.008-0.012 M.
[0027] In some embodiments, the elution solution is prepared using Hank's balanced salt solution and contains 0.05% trypsin, 4.0 mM sodium bicarbonate, and 0.5 mM tetrasodium EDTA.
[0028] In some embodiments, in step S112, the volume ratio of chloroform to methanol in the mixed solution is 1:1; 6 ml of the mixed solution is used for degreasing every 1 gram of bone powder.
[0029] In a second aspect, an embodiment of the present application provides a natural bone repair material with reorganized composition and structure, which is prepared by the preparation method described in the first aspect.
[0030] The embodiment of the present application provides a natural bone repair material with reorganized components and structure and a preparation method thereof. The natural cortical bone is crushed, defatted, decellularized and antigen-removed, and then mixed with PCL as printing ink. The natural bone repair material with reorganized components and structure is produced by a 3D printing method, so that allogeneic cortical bone can be fully utilized, solving the dilemma of shortage of allogeneic cancellous bone and low utilization rate of allogeneic cortical bone in clinical practice. At the same time, the antigens of the cortical bone powder are completely removed through crushing treatment and acid + enzyme decellularization treatment, and the produced bone repair material has good biocompatibility, is easy for tissue attachment and growth, and has a good repair effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The schematic diagram shows the process of preparing the composition and structure of the natural bone repair material provided by the present application. Figure 1 ;
[0032] Figure 2 The schematic diagram shows the process of preparing the composition and structure of the natural bone repair material provided by the present application. Figure 2 ;
[0033] Figure 3 The schematic diagram shows the process of preparing the composition and structure of the natural bone repair material provided by the present application. Figure 3 ;
[0034] Figure 4 A schematic diagram of the technical route of the composition and structure reorganization of natural bone repair materials provided by the present application is shown;
[0035] Figure 5 The results of α-Gal antigen detection of bovine bones under different treatment methods provided in the present application are shown;
[0036] Figure 6 The infrared spectroscopy FT-IR results of cattle bones under different treatment methods provided in this application are shown;
[0037] Figure 7 The decellularization test results of bovine bones under different treatment methods provided in the present application are shown;
[0038] Figure 8 The result diagram of the compressive strength of the product provided by the present application at different ratios is shown;
[0039] Fig. 9 The results of electron microscope scanning of the products provided by the present application at different ratios are shown;
[0040] Fig.10 The energy spectrum analysis results of the products provided by the present application at different ratios are shown;
[0041] Fig.11A schematic diagram showing the degradation rate of the product at different ratios provided by the present application is shown;
[0042] Fig.12 The composition identification result diagram of the product at different ratios provided by the present application is shown;
[0043] Fig.13 A schematic diagram of cell compatibility testing of products at different ratios provided by the present application is shown;
[0044] Fig.14 The BMP release of the products provided in this application at different ratios is shown;
[0045] Fig.15 The external view of the rat skull defect modeling process provided by the present application is shown;
[0046] Fig.16 A schematic diagram of the analysis of new bone provided by the present application is shown;
[0047] Fig.17 The morphological analysis results of the new bone provided by this application are shown Figure 1 ;
[0048] Fig.18 The morphological analysis results of the new bone provided by this application are shown Figure 2 ;
[0049] Fig.19 The morphological analysis results of the new bone provided by this application are shown Figure 3 ;
[0050] Fig. 20 The figure shows the expression analysis diagram of the specific markers of new bone provided in the present application. DETAILED DESCRIPTION
[0051] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present application. It is to be understood that the specific embodiments described herein are only used to explain the related applications, rather than to limit the present application. It should also be noted that, for ease of description, only the parts related to the related applications are shown in the accompanying drawings.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein are only for the purpose of describing the embodiments of this application and are not intended to limit this application.
[0053] In the following description, reference is made to “some embodiments”, which describe a subset of all possible embodiments, but it will be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.
[0054] At present, bone graft materials are divided into four categories: autologous bone, allogeneic bone, xenogeneic bone and artificial bone, which are introduced as follows:
[0055] (1) Autologous bone has the triple effects of bone induction, bone conduction and bone formation, and has the best bone formation effect, so it is regarded as the "gold standard" for bone defect repair. However, its source is limited and it is easy to cause complications such as persistent pain in the donor area.
[0056] (2) Allogeneic bone is an important material for replacing autologous bone, but it also has potential risks such as limited donor sources, certain immunogenicity and disease transmission (such as hepatitis B, AIDS, etc.). In particular, among natural bones, cancellous bone derived from human donated allogeneic bone has good pore size and porosity. After a certain decellularization and antigen removal treatment, it performs well in filling and repairing small bone defects through bone conduction. It has always been in short supply in clinical applications. However, its cortical bone is abnormally dense and has no pores. It is difficult to decellularize and remove antigens, resulting in a high risk of disease transmission. When used for large-segment bone repair, it has no pores, making it difficult for cells and blood vessels to grow into it. Its repair is limited to the surface in contact with the host bone, and it only serves as a temporary replacement, not a bone repair. It is often accompanied by a certain proportion of complications such as allogeneic bone fractures, bone resorption and infection. Therefore, allogeneic cortical bone is relatively rarely used in clinical practice and its utilization rate is not high.
[0057] (3) Xenogeneic bone has a wide range of sources, avoiding the shortcomings of limited sources of autologous bone and allogeneic bone, and has a natural structure similar to human bone. However, untreated xenogeneic tissue transplantation will cause strong rejection reactions, thus limiting its clinical application. Mild methods such as freezing, freeze-drying and decalcification are not effective in eliminating antigenicity. Although drastic methods such as deproteinization significantly reduce antigenicity, they also cause it to lose certain bioactive substances and mechanical strength. In addition, xenogeneic bone also has the risk of zoonotic disease transmission.
[0058] (4) Artificial bone refers to a bone substitute made using bioactive materials or chemical synthesis technology, mainly bioceramic materials: commonly used are biodegradable ceramics such as tricalcium phosphate (TCP), bioactive ceramics such as hydroxyapatite (HA), bioactive glass ceramics (BGC), biphasic calcium phosphate ceramics (HA / TCP), etc.; composite materials such as hydroxyapatite collagen composites, hydroxyapatite polyamide composites, etc. Artificial bone can provide a scaffold for bone formation, but its biological properties and degradation ability are far inferior to natural bone. These materials can be integrated into the host bone to varying degrees, but such materials only have osteoconductivity but no osteoinduction. They can only be used to repair small bone defects when used alone, and the bone formation rate and degradation time are uncontrollable. At the same time, whether the main raw materials of artificial bone are natural or synthetic, their composition is limited to "bionic" rather than "native".
[0059] The above bone graft materials are currently mainly used to repair small bone defects (≤4cm), and the effect is certain. For large bone defects (≥4cm), tissue engineering bone is considered to be the most promising repair method, and tissue engineering bone belongs to artificial bone. Scaffold materials, cells and growth factors are the three major elements of constructing tissue engineering bone; cell-type tissue engineering bone constructed by compounding cells and growth factors on scaffold materials or non-cellular tissue engineering bone constructed by compounding growth factors alone has better repair effect because of its biological activity.
[0060] At the same time, the rapid development of 3D printing technology has provided a more convenient and versatile technical means of choice and guarantee for the construction of tissue engineering bone. The overall strategy of 3D printing tissue engineering bone is: the raw material (printing ink) must have good biocompatibility, the raw material (printing ink) can be degraded in the body and its degradation rate matches that of osteogenesis, the raw material (printing ink) has bioprinting performance, and the printed tissue engineering bone has a certain mechanical strength, a suitable pore size and a certain porosity.
[0061] At present, the raw materials used for 3D printing tissue engineering scaffolds are divided into the following types: metals, ceramic materials, polymer materials, and mixtures of these substances. However, one problem faced by 3D printing ceramic bone repair materials is that they require high temperatures or secondary sintering, and can only prepare simple filling materials without cells or growth factors; at the same time, polymer materials have their own natural deficiencies that limit their application, including: unpredictable degradation, extremely poor mechanical properties, immune risks, and the need for cross-linking. These non-in vivo biological cross-linking in vitro artificial cross-linking effects are poor and have obvious side effects.
[0062] In summary, among all bone repair materials currently available, autologous bone is a perfect material but its source is limited. Natural (allogeneic, xenogeneic) cortical bone is abnormally dense and has no pores, making it difficult to decellularize and remove antigens. Direct transplantation and repair have poor effects and pose a high risk of disease transmission. A large amount of natural cortical bone cannot be fully utilized. No matter how much emphasis is placed on "bionics" in the main raw materials of artificial bone, they are not "native" and are far from the components of natural bone. In the preparation process of most artificial bones, there are technical defects such as artificial cross-linking rather than "in vivo biological cross-linking" which affects the repair effect.
[0063] In order to solve the above problems, the embodiments of the present application provide a method for preparing a natural bone repair material with reorganized composition and structure, which utilizes allogeneic cortical bone or xenogeneic cortical bone as printing ink and produces a natural bone repair material with reorganized composition and structure through a 3D printing method. Not only is the source of raw materials wide, but the antigens are also completely removed, and the resulting bone repair material has good biocompatibility and good repair effect.
[0064] The embodiments of the present application will be described in detail below with reference to the accompanying drawings.
[0065] In one embodiment, see Figure 1 , which provides a schematic flow chart of a method for preparing a natural bone repair material with recombinant components and structures. Figure 1 As shown, the preparation method comprises:
[0066] Step S111: crushing the natural cortical bone to produce cortical bone powder with a particle size of 300 to 500 microns.
[0067] Here, the natural cortical bone is allogenic bone or xenogeneic bone, which has a wide range of sources.
[0068] In the related art, cortical bone is abnormally dense and has no pores, so it is difficult to decellularize and remove antigens, resulting in a high risk of disease transmission. When used for large bone repair, it is difficult for cells and blood vessels to grow into it because of the lack of pores. Its repair is limited to the surface in contact with the host bone, and it only serves as a temporary replacement, not to mention bone repair; and it is often accompanied by a certain proportion of complications such as allogeneic bone fractures, bone absorption and infection. Therefore, allogeneic cortical bone is relatively rarely used clinically and its utilization rate is not high. However, the embodiment of the present application crushes the natural cortical bone to obtain cortical bone powder with a smaller particle size, so that the subsequent decellularization and antigen removal are more thorough, which is not only simple to operate, but also enables the cortical bone that was originally difficult to apply to bone transplantation to be used clinically, enriching the source of bone transplantation materials.
[0069] Step S112: using a mixture of chloroform and methanol to defatted the cortical bone powder to obtain defatted bone powder.
[0070] In one example, in step S112, the volume ratio of chloroform and methanol is 1:1; the ratio of the mixed liquid to the cortical bone powder is volume (ml) / weight (g) equal to 6:1, that is, 6 ml of the mixed liquid is used for degreasing every 1 gram of bone powder.
[0071] Step S113: decellularizing the defatted bone powder using an elution solution to obtain decellularized bone powder.
[0072] In one example, the elution solution is prepared using Hank's balanced salt solution containing 0.05% trypsin, 4.0 mM sodium bicarbonate, and 0.5 mM tetrasodium EDTA.
[0073] In this way, antigens in natural cortical bone are removed through decellularization and immunogenicity is eliminated, so that large sections of cortical bone, a widely available natural bone material, can be used as bone repair materials and bring about a wide range of clinical applications.
[0074] In addition, in terms of natural bone transplantation, the cellular component is the main antigen component, and the extracellular matrix without cells is difficult to match by any "bionic material". An important feature that distinguishes the extracellular matrix from other biomaterials is that it can provide a unique spatial structure and functional components; biological ink based on tissue or organ specific decellularization can reproduce and recreate the inherent microenvironmental niche of tissues and organs; mammalian tissues are composed of more than 300 matrix proteins and a variety of matrix regulatory enzymes, matrix-bound growth factors, and other matrix-related proteins. These proteins are involved in regulating the signal transmission between cells and structures, mechanics, biophysics and biochemistry. These biomolecules are naturally configured into a unique three-dimensional pattern. This highly organized extracellular matrix constitutes its innate properties and has tissue specificity; each component of the extracellular matrix performs tissue-specific functions, such as structural support, force transmission, regulation of cell attachment, differentiation, migration and proliferation, and regulation of developmental and evolutionary process functions and dynamic balance; in theory, cells produce extracellular matrix in the body, and in turn, the extracellular matrix acts on cells, activating several signal pathways to affect cell behavior, and the other In addition, the extracellular matrix carries a variety of enzymes, growth factors and other bioactive molecules that affect cell function; the decellularized extracellular matrix can be regarded as a reservoir of various bioactive signaling molecules, which maintains its function by maintaining the natural bone function and structural components. When used, these active substances are released and play a vital role in cell regulation to provide specific extracellular matrix-led repair and regeneration; the extracellular matrix is also a cell interconnecting substance, thereby regulating local cell behavior, such as cell attachment, differentiation, proliferation, migration and apoptosis; it participates in the release of growth factors, the transmission of mechanical mechanics and signal transduction and tissue polarization; the stress and strain mediated by the extracellular matrix regulates the proliferation phenotype of cells. This effect not only occurs in the developmental stage, but also throughout the process of tissue repair and regeneration. The most important protease family members responsible for ECM degradation, their degradation leads to the exposure of new recognition sites and the generation of new biological activities, which affects cell behavior and ultimately produces different biological processes such as: angiogenesis, angiogenesis inhibition, chemotaxis, cell adhesion, antibacterial, etc.
[0075] Therefore, after the cortical bone powder is defatted and decellularized in the embodiment of the present application, the extracellular matrix therein can still provide good auxiliary effects in the bone repair process and affect the overall bone repair process.
[0076] Step S114: washing the decellularized bone powder until the pH value is 7.3-7.5, and producing freeze-dried bone powder through freeze-drying.
[0077] Step S115: Grind the freeze-dried bone powder again to produce nano bone powder with a particle size less than or equal to 750 nanometers.
[0078] In this way, natural cortical bone is formed into defatted and decellularized nano bone powder through the above steps, and the particle size is nanometer level, so that cells and blood vessels can also attach and grow, and can be used for bone repair.
[0079] Step S2: Mix polycaprolactone PCL and nano bone powder to form a bone powder solution; use the bone powder solution to perform 3D printing to produce a natural bone repair material with reorganized components and structure.
[0080] It should be noted that polycaprolactone PCL is a semicrystalline hydrophobic degradable polyester with the characteristics of slow degradation under physiological conditions and good biocompatibility. PCL is mixed with nano-bone powder and used as printing ink for 3D printing, with good plasticity, processability and biocompatibility.
[0081] Overall, the embodiments of the present application have the following advantages: (1) The natural cortical bone is crushed and ground to the nanoscale, making the decellularization and antigen removal more thorough, breaking through the previous mindset that natural cortical bone powder is rarely used as a printing material, and changing the sought-after "highly bionic" material into the original natural "native" material; (2) With the help of 3D printing technology, structural reorganization, that is, cortical bone cancellization, is achieved, and the original cortical bone without voids is transformed into a cancellous bone close to nature, so that the natural cortical bone with poor repair effect and low utilization rate can show a repair effect similar to cancellous bone and can be fully used; (3) With the help of PCL's good thermoplasticity, through melt printing, the obtained product can achieve a mechanical strength close to that of natural cancellous bone without artificial cross-linking.
[0082] In the first specific embodiment, see Figure 2 , the aforementioned step S2 specifically includes:
[0083] Step S211: heating and dissolving PCL at 140° C. to form a PCL solution, adding nano bone powder to the PCL solution, and mixing to form a bone powder solution.
[0084] Exemplarily, the weight ratio of PCL to nano bone powder is 1:0.5-2.5.
[0085] Step S212: constructing a three-dimensional digital model of the bone defect scaffold.
[0086] Step S213: Fill the bone powder solution into the barrel of the 3D printer, and perform 3D single-line printing according to the three-dimensional digital model of the bone defect scaffold to produce a natural bone repair material with reorganized composition and structure.
[0087] Exemplarily, the parameters of 3D single-line printing are: wire diameter 0.3-0.5 mm, barrel temperature 100-130° C., platform temperature 40° C., pneumatic pressure 0.5 MPa, filling spacing 0.8-1.5 mm, speed 3 mm / s, rotation angle 90, number of rotations 2 times, layer height 0.25-0.45 mm.
[0088] Finally, the printed materials are soaked in pure water to remove contaminants, cleaned using ultrasound, dried naturally in a clean environment, and packaged and sterilized for later use.
[0089] In this way, by configuring PCL and nano-bone powder to form printing ink, the preparation of natural bone with common composition and structural reorganization was achieved, and the process of cortical bone cancellization was completed.
[0090] In some embodiments, collagen can be further extracted from the freeze-dried bone powder. Figure 3 , the method further comprises:
[0091] Step S121: Evenly mix the freeze-dried bone powder, hydrochloric acid solution and pepsin to produce a collagen solution.
[0092] Exemplarily, the volume of hydrochloric acid solution used per gram of bone powder is 90-120 ml, the volume of pepsin used per gram of bone powder is 80-120 mg, the mixing time is 90-100 hours, and the concentration of the hydrochloric acid solution is 0.008-0.012M.
[0093] Step S122: adding sodium chloride to the collagen solution, stirring until a white precipitate is precipitated, collecting the precipitate by centrifugation, and dissolving the precipitate in acetic acid to produce a solution to be treated.
[0094] Step S123: performing dialysis treatment on the solution to be treated to obtain collagen.
[0095] In a second specific embodiment, PCL, nano bone powder, bone collagen and recombinant human bone morphogenetic protein rh-BMP2 can be used to produce natural bone repair materials through 3D double-line printing to achieve the preparation of enhanced inductive components and structural reorganization of natural bones. Figure 3 , the aforementioned step S2 specifically includes:
[0096] Step S221: using polycaprolactone PCL and nano bone powder to form a bone powder solution, and using the bone powder solution as type A printing ink.
[0097] Exemplarily, the weight ratio of PCL to nano bone powder is 1:0.5-2.5;
[0098] Step S222: dissolving collagen in acetic acid to form collagen gel, and adding rh-BMP2 to the collagen gel to produce type B printing ink.
[0099] Exemplarily, 50 mg of collagen is added to every 1 ml of acetic acid, and 50 μg of rh-BMP2 is added to every 1 ml of bone gel solution.
[0100] Step S223: constructing a three-dimensional digital model of the bone defect scaffold.
[0101] Step S224: Fill type A printing ink into the high-temperature barrel and type B printing ink into the low-temperature barrel, and perform 3D double-line printing according to the three-dimensional digital model of the bone defect scaffold to produce a natural bone repair material with reorganized composition and structure.
[0102] In one example, the printing setting parameters for type A printing ink are as follows: wire diameter 0.3-0.5mm, barrel temperature 100-130℃, platform temperature 40℃, pneumatic pressure 0.5Mpa, filling spacing 0.8-1.5mm, speed 3mm / s, rotation angle 90°, rotation number 2 times, layer height 0.25-0.45mm; the printing setting parameters for type B printing ink are as follows: wire diameter 0.21-0.26mm, barrel temperature 23℃, platform temperature 40℃, pneumatic pressure 0.1-0.5Mpa, filling spacing 0.8-1.5mm, speed 3-15mm / s, rotation angle 90°, rotation number 2 times, layer height 0.25-0.45mm, and X and Y axis translation 0.5mm.
[0103] Finally, the components and structures produced by printing are quickly transferred to a -80°C refrigerator for pre-freezing for 4 hours, and then transferred to a freeze dryer for freeze drying, packaging, and sterilization.
[0104] In this way, on the basis of natural cortical bone cancellation, natural bone gel is used as a carrier to carry bone growth factors, and the bone conduction and bone induction theories are constructed simultaneously in product design to prepare non-cellular tissue engineering bone with inductive activity. Natural bone gel can also be used to carry bone growth factors and bone marrow stromal stem cells at the same time, and 3D bioprinting can be used to prepare complete tissue engineering bones with bone conduction, bone induction and bone formation functions to accelerate bone repair.
[0105] In summary, the embodiments of the present application propose a natural bone repair material with reorganized composition and structure and a preparation method thereof, wherein the abundant natural cortical bone is ground, decellularized and deantigenized, and then cancellized by 3D printing, so that the natural cortical bone, which originally had poor repair effect and low utilization rate, can show a repair effect similar to cancellous bone and can be fully utilized.
[0106] The following are specific embodiments.
[0107] See also Figure 4 , which shows a schematic diagram of the technical route of the composition and structure of the natural bone repair material provided in the embodiment of the present application. Figure 4 As shown, in the embodiment of the present application, fresh allogeneic cortical bone or xenogeneic bone is cryogenically crushed into bone powder of 300-500 microns in size, and after decellularization and antigen removal treatment, it is freeze-dried and ground again by a ball mill to make its particle size between 750 nanometers and below (hereinafter referred to as nano bone powder); a portion of the above-obtained bone powder is extracted with collagen according to the "acid + enzyme" method of this institute, freeze-dried, PCL is used as a bone powder adhesive, and bone gel is used as a carrier of bone growth factor BMP, and 3D bioprinting technology is used, or PCL and nano bone powder are printed in a ratio of (1:1; 1:2) by a single nozzle to become a natural bone repair material with components and structural reorganization without growth factors (single-line printing), or PCL and nano bone powder are printed in a ratio of (1:1; 1:2), 8% collagen gel carries an appropriate amount of BMP, and double nozzles and double lines are printed to become a natural bone repair material with enhanced inductive components and structural reorganization (double-line printing).
[0108] The following are specific instructions.
[0109] 1. Preparation of decellularized bone powder
[0110] Allogeneic / fresh calf / pig limb cortical bone (i.e. natural cortical bone), with the periosteum, soft tissue and bone marrow removed; low-temperature pulverization, bone powder sieved to form cortical bone powder, with a particle size of 300 to 500 microns.
[0111] 1. Cleaning: Soak the cortical bone powder in pure water (bone powder weight: pure water volume = 1:10), stir for 10 minutes and change the solution once, and wash 3 times in total to remove blood stains.
[0112] 2. Degreasing: Soak the bone powder in a mixed solution formed by a volume ratio of chloroform to methanol = 1:1, the specific ratio is: bone powder (g): mixed solution (ml) = 1:6, degreasing for 4 hours to produce defatted bone powder;
[0113] 3. Decellularization: Discard the liquid, soak the bone particles with an appropriate amount (1000 mL) of decellularization solution containing 0.05% trypsin, 4.0 mM sodium bicarbonate and 0.5 mM tetrasodium EDTA prepared with Hank's balanced salt solution, and shake at 37°C, 200 rpm, for 2 hours to produce decellularized bone powder.
[0114] 4. Wash the decellularized bone powder again with pure water (bone powder weight: pure water volume = 1:10) for 3 times until the pH value is equal to 7.4.
[0115] 5. Drain the washed decellularized bone powder, pre-freeze it in a -40°C refrigerator for 4 hours, and transfer it to a freeze dryer for freeze-drying and sealing to produce freeze-dried bone powder.
[0116] See also Figure 5 , which respectively show the α-Gal antigen detection results (sampling Elisa detection method) of cattle bones treated with fresh cattle bones, literature method, bone bank method and improved method (the method used in the examples of the present application, i.e., the method described in steps S111 to S113). Figure 5 The results showed that the improved method was the most effective in removing α-gal antigen, with an antigen removal rate of 92.13±2.02%.
[0117] See also Figure 6 , which shows the infrared spectra FT-IR results of fresh cattle bones, cattle bones processed by literature method, bone bank method and improved method. Figure 6 As shown, 2957cm -1 、2917cm -1 and 2851cm -1 The absorption peak at 1740cm is attributed to the CH stretching vibration mode in fatty acid compounds. -1 1456cm is the typical absorption peak of the stretching vibration mode of the carbonyl C=O of acid and ester compounds. -1 and 1380cm -1 The absorption peak composition at is relatively complex, including structures such as CH, C=C and C-OH, which are mainly derived from fatty acids, phenols and alcohol compounds. The above are the main characteristic peaks of fat and protein. The characteristic peaks of the bone bank method and the improved method disappear here, indicating that defatting and deproteinization are effective.
[0118] See also Figure 7 , which respectively show the results of decellularization test of bovine bones processed by literature method, bone bank method and improved method. Figure 7 As shown, there are trace amounts of genetic material dsDNA in the cattle bones treated by different methods. The dsDNA contents of cattle bones treated by the literature method, bone bank method and improved method are 22.204ng / mg, 60.468ng / mg and 20.231ng / mg respectively. The dsDNA content in cattle bones treated by the literature method and the improved method is lower than the decellularization detection standard in the literature (50ng / mg), and the dsDNA content in the bone bank method is slightly higher than the standard, indicating that the improved method used in the preparation of the product is the most effective for decellularization.
[0119] 2. Collagen Extraction
[0120] 1. Weigh a certain amount of freeze-dried bone powder and put it into an electromagnetic stirrer at a ratio of 1g dry bone powder: 100ml hydrochloric acid solution (concentration of 0.01M): 100mg pepsin and stir continuously for 96 hours to produce a collagen solution.
[0121] 2. Add sodium chloride at 1 / 10 of the volume of the collagen solution, stir manually until a white precipitate is precipitated, pour the precipitate solution into a centrifuge tube and centrifuge at low temperature and high speed at 12,000 rpm for 15 minutes;
[0122] 3. Discard the supernatant and collect the precipitate. Dissolve the precipitate with 0.01M acetic acid and place it in a dialysis bag for dialysis. Add 20 times deionized water and change it every 8 hours for a total of 48 hours. Collect the dialyzed solution in a container and pre-freeze it at -40℃.
[0123] 4. Freeze-dry in a low-temperature freeze dryer for 24 hours to obtain collagen and seal it for storage.
[0124] 3. Preparation of Nano-bone Powder
[0125] 1. Weigh an appropriate amount of the above-prepared decellularized and antigen-free bone powder (300-500 microns) and add it to the tank of a planetary zirconia ball mill. The volume ratio of bone powder to zirconia balls (large, medium and small) is 1:1.
[0126] 2. Grind at room temperature for about 16 hours.
[0127] 3. Sieve and select particles of 750 nanometers and below to form nano bone powder;
[0128] 4. Packaging and irradiation sterilization.
[0129] 4. Preparation of natural bone with composition and structure reconstruction (3D printing)
[0130] 1. Preparation of natural bone with common composition and structure (cortical cancellous bone)
[0131] 1.1 Printing ink preparation
[0132] First, heat and dissolve PCL at 140° C., and after PCL is dissolved, add nano-bone powder, with the weight ratio of PCL to nano-bone powder being 1:0.5-2.5; and mix well in a mixer.
[0133] 1.2 Modeling
[0134] Individualized modeling: First, scan the bone defect where the material is placed using CT or MRI, then build a three-dimensional digital model of the target bone defect scaffold and export it in STL format;
[0135] General modeling: Use CAD modeling software to build a three-dimensional digital model and export it in STL format.
[0136] 1.3 Printing parameter setting and printing
[0137] The above printing ink is filled in the barrel and printed according to the following parameters:
[0138] Wire diameter 0.3-0.5mm, barrel temperature 100-130℃, platform temperature 40℃, pneumatic pressure 0.5Mpa, filling spacing 0.8-1.5mm, speed 3mm / s, rotation angle 90°, rotation times 2 times, layer height 0.25-0.45mm.
[0139] 1.4 Post-printing processing
[0140] The printed material is soaked in pure water for 10 minutes, ultrasonically cleaned for 10 minutes, dried naturally in a clean environment, packaged, and sterilized.
[0141] 2. Preparation of natural bone with enhanced inductive components and structural reorganization (dual-line printing)
[0142] 2.1 Printing ink preparation
[0143] 2.1.1 Type A printing ink preparation
[0144] First, heat and dissolve PCL at 140° C., and after PCL is dissolved, add nano-bone powder, with the weight ratio of PCL to nano-bone powder being 1:0.5-2.5; and mix well in a mixer.
[0145] 2.1.2B type printing ink preparation
[0146] (1) Dissolve collagen in 0.05 M acetic acid at 4°C, with the volume / weight ratio of acetic acid to collagen being approximately 1 mL / 50 mg;
[0147] (2) rh-BMP2 was added to the above collagen gel, and the ratio of collagen gel to BMP was: BMP (μg) / bone gel (ml) = 50 μg / ml;
[0148] (3) The above-mentioned BMP-containing bone gel is loaded into a screw-mouth syringe and two syringes are connected using a Luer connector, and the syringes are pushed repeatedly for 15 minutes to mix the collagen and bone induction growth factor evenly;
[0149] (4) Modeling: Use CAD modeling software to build a three-dimensional digital model and export it in STL format;
[0150] 2.3 Printing parameter setting and printing
[0151] The above-mentioned type A printing ink is filled into the high-temperature barrel, and the type B printing ink is filled into the low-temperature barrel, and printing is performed according to the following parameters: the setting parameters of model A are wire diameter 0.3-0.5mm, barrel temperature 100-130℃, platform temperature 40℃, pneumatic pressure 0.5Mpa, filling spacing 0.8-1.5mm, speed 3mm / s, rotation angle 90°, rotation times 2 times, layer height 0.25-0.45mm;
[0152] The setting parameters of model B are as follows: wire diameter 0.21-0.26 mm, barrel temperature 23 °C, platform temperature 40 °C, pneumatic pressure 0.1-0.5 MPa, filling spacing 0.8-1.5 mm, speed 3-15 mm / s, rotation angle 90°, rotation times 2 times, layer height 0.25-0.45 mm, and X and Y axis translation 0.5 mm.
[0153] 2.4 Post-printing processing
[0154] The printed materials were quickly transferred to a -80°C refrigerator for pre-freezing for 4 hours and then transferred to a freeze dryer for freeze drying, packaging, and sterilization.
[0155] See also Figure 8 , which is a result diagram of the compressive strength of the product (i.e., natural bone repair material) at different ratios provided in the embodiments of the present application. Figure 8 As shown, the compressive strength of the product printed by the pure PCL group was 67.72±9.09MPa, the compressive strength of the product printed by the PB2:1 group (i.e. PCL: nano bone powder Bone=2:1) was 51.76±7.50MPa, the compressive strength of the product printed by the PB 1:1 group (i.e. PCL: nano bone powder Bone=1:1) was 46.95±8.14MPa, the compressive strength of the product printed by the PB 3:2 group (i.e. PCL: nano bone powder Bone=3:2) was 41.05±8.14MPa, the compressive strength of the product printed by the PB1:2 group (i.e. PCL: nano bone powder Bone=1:2) was 38.04±6.58MPa, and the compressive strength of the product printed by bovine cancellous bone Bone was 6.19±1.21Mpa. It can be seen that as the PCL content increases, the compressive strength of the product increases, and the compressive strength of the product is greater than the compressive strength of human cancellous bone (between 2-12MPa), indicating that the product can be used to repair bone defects.
[0156] See also Fig. 9 , which is the result of electron microscope scanning of the product (specifically the scaffold, which is also the aforementioned natural bone repair material with reorganized components and structure) at different ratios provided in the embodiments of the present application. Fig. 9 As shown, the more bone meal there is in the product, the rougher its surface.
[0157] See also Fig.10 , which is the energy spectrum analysis result of the product (i.e., natural bone repair material) at different ratios provided in the embodiments of the present application. Among them, Fig.10 (a) is the electron microscope scanning result, which shows that the surface of the mixed product is relatively rough, which is conducive to the adhesion of cells and bioactive factors. Fig.10(b) in the figure is the result display of energy spectrum analysis, which shows that the mixed product mainly contains components such as C, O, P, and Ca, indicating that the product is successfully mixed with PCL and bone powder.
[0158] See also Fig.11 , which is a schematic diagram of the degradation rate of the product (i.e., natural bone repair material) at different ratios provided in the embodiments of the present application. Fig.11 As shown in the figure, with the increase of bone powder, the degradation rate of the product accelerated. After 4 weeks of degradation, the degradation rate of the PB 1:2 group reached 9.802±0.280%, and the degradation rate of the PB 3:2 group reached 8.854±0.237%. There was no significant difference between the PB 3:2 group and the PB 1:2 group.
[0159] See also Fig.12 , which is a diagram of the component identification results of the product (i.e., natural bone repair material) at different proportions provided in the examples of the present application. Fig.12 (a) is specifically an infrared spectrum, where 2945 cm -1 、2866cm -1 、1724cm -1 、1178cm -1 The characteristic peak of PCL is 1635cm -1 、1534cm -1 The peak at the bottom is the characteristic peak of cattle bone, indicating that the product has successfully mixed bone meal and PCL; Fig.12 (b) in the figure is specifically an XRD spectrum, where 21.4° and 23.8° are characteristic peaks of PCL, and 32° is a characteristic peak of bovine bone.
[0160] See also Fig.13 , which is a schematic diagram of the cell compatibility detection of the product (i.e., natural bone repair material) at different proportions provided in the examples of the present application. Fig.13 (a) is a live-dead staining result of bone marrow mesenchymal stem cells (BMSC) on the scaffolds printed with products of different proportions. Fig.13 (b) specifically shows the percentage of live BMSC cells on the scaffolds printed with products in different ratios, indicating that the materials in each group have no cytotoxicity.
[0161] Combining the results of material characterization and cell experiments, the PCL: bone powder 3:2 group was screened as the best ratio. This group has good biocompatibility and degradation rate, as well as good compressive strength (41.05±8.14MPa), which can provide mechanical support for new bone tissue. This ratio of scaffolds was used to load rhBMP-2 (i.e., double-line printing) for subsequent experiments.
[0162] See also Fig.14, which is the BMP release of the products (i.e., natural bone repair materials) at different ratios provided in the embodiments of the present application, wherein PCL / rhBMP-2 refers to a bone repair scaffold printed with pure PCL loaded with rhBMP-2, and PB / rhBMP-2 refers to a bone repair scaffold printed with a mixture of PCL and PB (PCL:PB=3:2) loaded with rhBMP-2, such as Fig.14 As shown in the figure, the release of PB / rhBMP-2 can last for 21 days, while the PCL / rhBMP-2 scaffold has almost completely released rhBMP-2 on the 14th day, and the PCL / rhBMP-2 scaffold has almost burst release within 2 hours, while the product can release relatively stably. Therefore, the in vitro release experiment of rhBMP-2 shows that the product can release BMP more stably and continuously.
[0163] See also Fig.15 , which is an appearance diagram of the rat skull defect modeling process provided by the implementation of this application. The control group was not implanted with a scaffold, while the experimental group was implanted with a scaffold made of the aforementioned bone repair material. The following four groups of scaffold products were analyzed for their bone defect repair effects. The four groups of products are: (1) Control, which refers to the control group without a scaffold; (2) PCL, which refers to a scaffold formed by printing with pure PCL implanted; (3) PCL-rhBMP, which refers to a scaffold formed by printing after implanting pure PCL loaded with rhBMP; (4) B-rhBMP, which refers to a scaffold formed by printing after implanting a mixture of PCL:PB=3:2 loaded with rhBMP (i.e., the aforementioned double-line printing). The results are shown in the figure. Figure 16 to Figure 19 shown.
[0164] See also Fig.16 , which is a schematic diagram of the analysis of new bone provided in the implementation of this application. Fig.16 (a) is the Micro-CT three-dimensional reconstruction image; Fig.16 (b) in the figure is the result of BV / TV (bone volume fraction); Fig.16 (c) in the figure is the result of Tb.Th (trabecular bone thickness); Fig.16 (d) in the figure is the result of Tb.Sb (trabecular separation).
[0165] See also Figure 17 to Figure 19 , which is a diagram of the morphological analysis results of the new bone provided in the implementation of this application. Fig.17 The Masson staining results of the skull defect model at 4 weeks and 12 weeks after surgery are shown respectively; Fig.18 The HE staining results of the skull defect model at 4 weeks and 12 weeks after surgery are shown respectively; Fig.19 The VG staining results of the skull defect model at 4 weeks and 12 weeks after surgery are shown respectively.
[0166] See also Fig. 20, which is an expression analysis diagram of specific markers of new bone provided in the implementation of this application. Fig. 20 (a) shows the immunohistochemical staining results of osteopontin OPN in the skull defect model 4 weeks after surgery. Fig. 20 (b) shows the immunohistochemical staining results of osteocalcin (OCN) in the skull defect model 12 weeks after surgery. Fig.15 (c) is the positive result ratio of OPN in the skull defect model 4 weeks after surgery. Fig.15 (d) shows the positive result ratio of OCN in the skull defect model 4 weeks after surgery.
[0167] according to Figures 16 to 20 , indicating that the repair effect of the double-line printed natural bone repair material provided in the embodiment of the present application is the most significant.
[0168] In another embodiment of the present application, a natural bone repair material prepared by the above method is provided.
[0169] Details not disclosed in the embodiments of the present application may be understood by referring to the description of the aforementioned embodiments.
[0170] The above are only preferred embodiments of the present application and are not intended to limit the protection scope of the present application.
[0171] It should be noted that, in this application, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0172] The serial numbers of the above-mentioned embodiments of the present application are for description only and do not represent the advantages or disadvantages of the embodiments.
[0173] The methods disclosed in several method embodiments provided in this application can be arbitrarily combined without conflict to obtain new method embodiments.
[0174] The features disclosed in several product embodiments provided in this application can be arbitrarily combined without conflict to obtain new product embodiments.
[0175] The features disclosed in several method or device embodiments provided in this application can be arbitrarily combined without conflict to obtain new method embodiments or device embodiments.
[0176] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a natural bone repair material with reorganized components and structure, characterized in that: The method comprises: Step S111: crushing the natural cortical bone to produce cortical bone powder with a particle size of 300 to 500 microns; wherein the natural cortical bone is allogenic bone or xenogeneic bone; Step S112: using a mixture of chloroform and methanol to defatted the cortical bone powder to obtain defatted bone powder; Step S113: performing a decellularization treatment on the defatted bone powder using an elution solution to obtain decellularized bone powder; Step S114: washing the decellularized bone powder until the pH value is 7.3-7.5, and producing freeze-dried bone powder by freeze-drying; Step S115: grinding the freeze-dried bone powder again to produce nano bone powder with a particle size of less than or equal to 750 nanometers; Step S2: mixing polycaprolactone PCL and the nano bone powder to form a bone powder solution; and performing 3D printing processing using the bone powder solution to produce a natural bone repair material with reorganized components and structure.
2. The preparation method according to claim 1, characterized in that: The step S2 specifically includes: Step S211: heating and dissolving PCL at 140° C. to form a PCL solution, adding the nano bone powder to the PCL solution, and mixing to form the bone powder solution; wherein the weight ratio of PCL to the nano bone powder is 1:0.5-2.5; Step S212: constructing a three-dimensional digital model of the bone defect scaffold; Step S213: Fill the bone powder solution into the barrel of a 3D printer, and perform 3D single-line printing according to the three-dimensional digital model of the bone defect scaffold to produce the natural bone repair material with reorganized components and structure.
3. The preparation method according to claim 2, characterized in that: For step S213, the parameters of the 3D single-line printing are: Wire diameter 0.3-0.5mm, barrel temperature 100-130℃, platform temperature 40℃, pneumatic pressure 0.5Mpa, filling spacing 0.8-1.5mm, speed 3mm / s, rotation angle 90, rotation times 2 times, layer height 0.25-0.45mm.
4. The preparation method according to claim 1, characterized in that: The method further comprises: Step S121: uniformly mixing the freeze-dried bone powder, hydrochloric acid solution and pepsin to produce a collagen solution; Step S122: adding sodium chloride to the collagen solution, stirring until a white precipitate is precipitated, collecting the precipitate by centrifugation, and dissolving the precipitate in acetic acid to produce a solution to be treated; Step S123: performing dialysis treatment on the solution to be treated to obtain collagen.
5. The preparation method according to claim 4, characterized in that: The step S2 specifically includes: Step S221: using polycaprolactone PCL and the nano bone powder to form a bone powder solution, and using the bone powder solution as type A printing ink; wherein the weight ratio of the PCL to the nano bone powder is 1:0.5-2.5; Step S222: dissolving the collagen in acetic acid to form a collagen gel, and adding recombinant human bone morphogenetic protein rh-BMP2 to the collagen gel to produce type B printing ink; wherein 50 mg of collagen is added to every 1 ml of the acetic acid, and 50 μg of rh-BMP2 is added to every 1 ml of the bone gel solution; Step S223: constructing a three-dimensional digital model of the bone defect scaffold; Step S224: Fill the type A printing ink into a high-temperature barrel and the type B printing ink into a low-temperature barrel, and perform 3D double-line printing according to the three-dimensional digital model of the bone defect scaffold to produce the natural bone repair material with reorganized composition and structure.
6. The preparation method according to claim 5, characterized in that: In step S224, The printing setting parameters of type A printing ink are wire diameter 0.3-0.5mm, barrel temperature 100-130℃, platform temperature 40℃, pneumatic pressure 0.5Mpa, filling spacing 0.8-1.5mm, speed 3mm / s, rotation angle 90°, rotation times 2 times, layer height 0.25-0.45mm; The printing setting parameters for type B printing ink are wire diameter 0.21-0.26mm, barrel temperature 23℃, platform temperature 40℃, pneumatic pressure 0.1-0.5Mpa, filling spacing 0.8-1.5mm, speed 3-15mm / s, rotation angle 90°, rotation number 2 times, layer height 0.25-0.45mm, and X and Y axis translation 0.5mm.
7. The preparation method according to claim 4, characterized in that: In step S121, the volume of hydrochloric acid solution used for every gram of bone powder is 90-120 ml, the volume of pepsin used for every gram of bone powder is 80-120 mg, the mixing time is 90-100 hours, and the concentration of the hydrochloric acid solution is 0.008-0.012M.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The elution solution was prepared using Hank's balanced salt solution and contained 0.05% trypsin, 4.0 mM sodium bicarbonate and 0.5 mM tetrasodium EDTA.
9. The preparation method according to claim 1, characterized in that: In step S112, the volume ratio of chloroform to methanol in the mixed solution is 1:1; 6 ml of the mixed solution is used for degreasing every 1 gram of bone powder.
10. A natural bone repair material with reorganized components and structure, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Implant and method for manufacturing mandibular implant with PEKK (polyetherketoneketone) supporting and fixing units and tissue engineering growth unit
CN106580520A
Bone repairing material for 3D printing and method for preparing bone repairing scaffold
CN108310465A
Porous PCL / collagen artificial periosteum with directional drug sustained release function and preparation method thereof
CN113171496A
Composite biomaterial
CN114222812A
Artificial blood vessel and preparation method thereof
US20170325933A1